Concept and Evolution in 3D Printing for Excellence in Healthcare - Sinha, Priyank; Lahare, Preeti; Sahu, Meena; Cimler, Richard; Schnitzer, Marek; Hlubenova, Jana; Hudak, Radovan; Singh, Namrata; Gupta, Bhanushree; Kuca, Kamil (Current Medicinal Chemistry, 2025)
Three-dimensional printing (3DP) has gained popularity among scientists and researchers in every field due to its potential to drastically reduce energy costs for the production of customized products by utilizing less energy-intensive machines as well as minimizing material waste. The 3D printing technology is an additive manufacturing approach that uses material layer-by-layer fabrication to produce the digitally specified 3D model. The use of 3D printing technology in the pharmaceutical sector has the potential to revolutionize research and development by providing a quick and easy means to manufacture personalized one-off batches, each with unique dosages, distinct substances, shapes, and sizes, as well as variable release rates. This overview addresses the concept of 3D printing, its evolution, and its operation, as well as the most popular types of 3D printing processes utilized in the health care industry. It also discusses the application of these cutting-edge technologies to the pharmaceutical industry, advancements in various medical fields and medical equipment, 3D bioprinting, the most recent initiatives to combat COVID-19, regulatory frameworks, and the major challenges that this technology currently faces. In addition, we attempt to provide some futuristic approaches to 3DP applications.
Keywords: inkjet